The effect of Glyptotermes montanus termites supplementation as protein source in the diet for broiler strian Rokky-301 - Uhi, Harry T; Jachja, Jajat; Mutia, Rita; Nandika, Dodi (Indonesian Journal of Animal and Veterinary Sciences, 2001)
Termites (Isoptera) as one of local feed in several places in Indonesia just like Irian jaya, is available, easy to find and having protein in a high level. Termites nest which high about 0,5-2 metres above ground is easy to find at all low area merauke which having land areal about 20.000 ha, otherwise in other distrik, it can easily to find in a forest especialy in a new open land for Agriculture and transmigration. The purpose of this experiment was to study the effects of Glyptotermes montanus Kemner termites suplementation as protein resource in the diet of broiler strain Rokky-301. One hundred eighty DOC Rokky-301 were randomly divided in to five treatment with three replicates of 12 chickens each. The treatment diets were basal diet (R0), basal diet + fresh termites 0,5% (R1), basal diet + fresh termites 1% (R2), basal diet + fresh termites 1,5% (R3), and Comercial diet (R4) as positive control. The chickens were fed the treatment diets over 50 days. The results showed that the chicken fed R3 diet had significantly higher body weight gain than did chicken fed other diets except for chicken fed commercial diet (R4). Feed consumption of chicken fed R0 diet was significantly higher than other treatment diets. However 1,5% fresh termites suplementation (R3) significantly reduced feed consumption. Basal diet (R0) had highest feed conversion compared to other treatment diets. However 1,5% fresh termites suplementation (R3) was significantly improved feed conversion compared to other treatment. Â  Key word: Body weight gain, Glyptotermes montanus termites, broiler strain Rokky-301